Effect of Computer-Based Blended Learning Strategy on Secondary School Chemistry Students Retention in Individualised and Collaborative Learning Settings in Minna, Nigeria - M.S. Suleiman; B.M. Salaudeen; O.C. Falode (University of Sofia, 2017)
This study investigated effects of Computer-based blended learning strategy on Secondary School Chemistry students retention in individualised and collaborative learning settings in Minna, Niger State, Nigeria. The study adopted a quazi-experimental design and three research questions and three null hypotheses were formulated to guide the study. Multi-staged sampling procedure was used to select a total of 120 (71 female & 49 male) students from three co-educational schools within the study area. The selected students were randomly assigned to experimental group I (Computer based blended learning in individualised setting) experimental group II (Computer based blended learning in collaborative setting) and the control group (lecture method). A multiple-choice question items on Chemistry that was developed, validated by the Chemistry experts was pilot-tested and a reliability coefficient of 0.74 was obtained using test re-test method. The achievement test was administered as instrument for data collection to students as pre-test, post-test and retention test. The data obtained from the administration of research instruments were analysed using Analysis of Covariance (ANCOVA) statistics. The results indi-cated that Computer Based Blended learning strategy improved students retention in chemistry in collaborative learning settings better than in individualized learning setting and in lecture method. It was therefore recommended among others that students should be exposed to Computer based blended learning strategy in collaborative learning setting in order to aid their retention of chemistry concepts.